2004
DOI: 10.1148/radiol.2302020828
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging of Gastric Adenocarcinoma: Comparison of Helical CT and Endoscopic US

Abstract: Compared with endoscopic US, helical CT focused on the stomach provides valuable results regarding T and N staging in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
150
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(176 citation statements)
references
References 28 publications
8
150
2
11
Order By: Relevance
“…One of the most useful methods for gastric cancer staging is computed tomography, which accepts as a positive lymph node those up to 10 mm size (5,6). Therefore, we have considered 10 mm lymph node size as differentiation criteria of each study group.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most useful methods for gastric cancer staging is computed tomography, which accepts as a positive lymph node those up to 10 mm size (5,6). Therefore, we have considered 10 mm lymph node size as differentiation criteria of each study group.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to get high quality images of the gastric wall and anatomical perigastric structures by means of endoscopic ultrasonography, therefore, it is being used with high diagnostic yield in the loco-regional staging of the gastric cancer (3)(4)(5)(6). However, the importance that these have for everyday medical practice has been cause for debate.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging findings vary depending on the type and grade of the tumor, including diffuse or segmental thickening with intravenous contrast enhancement, masses, ulceration, and loss of distensibility. 16,19 UGE is the method of choice for definitive diagnosis, because it is more sensitive and allows biopsies to be performed for histopathologic analysis. 16 Endoscopic ultrasonography is currently the best method for assessing the primary tumor as well as evaluating the local extent of the tumor and the presence of compromised regional lymph nodes.…”
mentioning
confidence: 99%
“…16 Endoscopic ultrasonography is currently the best method for assessing the primary tumor as well as evaluating the local extent of the tumor and the presence of compromised regional lymph nodes. 19 Recent studies have demonstrated the role of MRI in the diagnosis of early gastric carcinomas that are not seen on other imaging tests. 20 The rarity of gastric cancer in children makes this diagnosis a very remote possibility among pediatricians.…”
mentioning
confidence: 99%